The relationship of Arabic meters to Semitic meters: A morphological-semantic study - Mahdi , Iman (Al-Adab Journal, 2025)
The research studied some of the meters that the Arabic language shares with its fellow Semitic languages, showing the changes that occur in these meters as a result of the addition to their origin, examining their significance in Arabic and its sisters, highlighting the scarcity and abundance of use in it, presenting the opinions of Arab researchers and orientalists who They gave their opinion in this field, revealing that some of them differed from each other in some places, supporting some opinions, criticizing others, drawing on different sources, and dividing them into various paragraphs, beginning with the definition of the Semitic languages. He passes through its،original place and then its divisions, and goes back to the knowledge of the first Arab scholars about some of them, and discusses in detail the meters that are its main subject, dividing them into five types between abstract and more, and concluding with a set of results that he reached.